Impact of Therapy in Patients with Hematologic Malignancies on Seroconversion Rates After SARS-CoV-2 Vaccination - Guven, Deniz C; Sahin, Taha K; Akın, Serkan; Uckun, Fatih M (The oncologist (Dayton, Ohio), 2022)
Abstract Introduction The leading professional organizations in the field of hematology have recommended severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) vaccination for all patients with hematologic malignancies notwithstanding efficacy concerns. Here we report a systematic literature review regarding the antibody response to SARS-CoV-2 vaccination in patients with hematologic malignancies and its key determinants. Methods We conducted a systematic search of original articles evaluating the seroconversion rates with SARS-CoV-2 vaccines in hematological malignancies from the PubMed database published between April 1, 2021 and December 4, 2021. Calculated risk differences (RD) and 95% confidence intervals (CI) to compare seroconversion rates between patients with hematologic malignancies versus healthy control subjects used the Review Manager software, version 5.3. Results In our meta-analysis, we included 26 studies with control arms. After the first dose of vaccination, patients with hematologic malignancies had significantly lower seroconversion rates than controls (33.3% vs 74.9%; RD: −0.48%, 95% CI: −0.60%, −0.36%, P < .001). The seroconversion rates increased after the second dose, although a significant difference remained between these 2 groups (65.3% vs 97.8%; RD: −0.35%, 95% CI: −0.42%, −0.28%, P < .001). This difference in seroconversion rates was particularly pronounced for Chronic Lymphocytic Leukemia (CLL) patients (RD: −0.46%, 95% CI: −0.56, −0.37, P < .001), and for patients with B-lineage leukemia/lymphoma treated with anti-CD20 antibodies (RD: −0.70%, 95% CI: −0.88%, −0.51%, P < .001) or Bruton Tyrosine Kinase Inhibitors (BTKi; RD: −0.63%, 95% CI: −0.85%, −0.41%, P < .001). The RD was lower for patients under remission (RD: −0.10%, 95% CI: −0.18%, −0.02%, P = .01). Conclusion The seroconversion rates following SARS-CoV-2 vaccination in patients with hematologic malignancies, especially in CLL patients and patients treated with anti-CD20 antibodies or BTKi, were significantly lower than the seroconversion rates in healthy control subjects. Effective strategies capable of improving vaccine efficacy in these vulnerable patient populations are urgently needed.